8th April: Easter Sunday: Luke 24.13-49 - McGlynn, Moyna (The expository times, 2012)
The article offers information on the Jesus Christ's journey to Emmaus after resurrection. It states the Christ appeared in front of his two disciples while coming from Jerusalem to Emmaus. It mentions that Jesus there divides a loaf of bread between the two disciples, and it was then when the disciples recognized Christ.